Pengaruh Fitur Artificial Intelligence: Chatbot, Visual Search dan Virtual Try On Terhadap Minat Beli Konsumen Pada e-Commerce - Dewi, Multi Sari; Khasaanah, Aulia Uswatun (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2026)
The development of Artificial Intelligence (AI) technology in e-commerce encourages the improvement of interactive and personalized digital shopping experiences. This study aims to determine the influence of chatbot, visual search, and virtual try-on features on consumer buying interest on e-commerce platforms. The research method used was quantitative descriptive association with purposive sampling techniques on 154 respondents who used e-commerce users who had used the three AI features. Data collection was carried out through the distribution of online questionnaires, and data analysis using multiple linear regression with the help of SPSS software. The results of the study show that the three AI features have a positive and significant influence on consumer buying interest. Virtual try-ons are the most dominant feature influencing buying interest, followed by visual search and chatbots. Simultaneously, the three features contributed 80.67% to consumer buying interest. These findings confirm that the use of AI features in e-commerce not only improves search efficiency and shopping convenience, but also drives more convincing purchasing decisions.